Epidemic Prevention During Work Resumption: A Case Study of One Chinese Company's Experience - Zhang, Quan; Wu, Yijin; Li, Meiyu; Li, Linzi (Frontiers in Public Health, 2021)
Background The COVID-19 epidemic not only brings challenges to the health of people all over the world, but also impacts the global economy and employment. Therefore, promoting industry and business to resume work safely has become an important step to be taken by all countries in overcoming the economic recession and restarting growth. Objective This study aims to elaborate on epidemic prevention measures a Chinese company (Company C) took during work resumption. Methods In this study, we used a case study design, with field research method applied to data collection and analysis, Results It has been identified that Company C took a range of effective measures to prevent the outbreak of COVID-19 inside the company, which involve work resumption preparation (information survey, health training, work resumption plan, epidemic prevention plan), facilities management, materials management, employee activity management, and so on. Conclusion When the COVID-19 epidemic was initially controlled in February, the Chinese government allowed enterprises to resume work voluntarily, which did not bring about a rebound in the epidemic. One important reason is that Chinese enterprises have taken effective measures to prevent the spread of the COVID-19 virus. Company C’s practices could shed some light on how companies in Western countries resume their work during the COVID-19 pandemic.